Odpowiedzi

2010-02-15T20:46:55+01:00
3(1-2x)>4x
3-6x>4x
-6x-4x>-3
-10x>-3|:(-10)
x<0,3


(4x-5)(2+9)>(6x-1)²
8x+36-10-45>36x-1
8x-36x>(-1)-36+10+45
-28x>18|:(-28)
x<(-18/28)


-4(2x-5)=2(3x+7)
-8x+20=6x+14
-8x-6x=14-20
-14x=(-6)|:(-14)
x= (-6/14)
x= (-3/2)
x= (-1½)
1 5 1
2010-02-15T20:48:39+01:00
1)
3(1 - 2x) > 4x
3 - 6x > 4x
-6x -4x > -3
-10 x > -3 \ - 10
x>0,3

2)
(4x - 5)(2+ 9) > (6x - 1)2
8x + 36x - 10 - 45 > 24x +1
8x +36x - 24x > 1+ 10 +45
20x > 56 \20
x>2,8

3)
-4(2x - 5) = 2(3x +7 )
-8x + 20 = 6x + 14
-8x - 6x = -20 +14
-14x = -6 \ -14
x = 0,4
1 5 1